Hydraulic model study of an alternative sediment control system for Nathpa-Jhakri project, India - Gupta, Subhash Chand; Preecha Kamronrithisorn; Gupta, Ashim Das; Chauhan, Roshan Lal; Paudyal, Guna N.; The Government of the United Kingdom (Bangkok : Asian Institute of Technology, 1989)
In the Modified Project Report (1986) of Nathpa-Jhakri hydroelectric project, an underground desilting complex with four parallel chambers, each 350 m x 25 m x 38 m has been proposed. Since this project is located in the Himalayan region consisting of the youngest rocks in the world and geology of this region is unpredictable, provision of suitable desilting arrangement will be of vital importance. It is anticipated that underground construction of these huge chambers, both in respect of span and length would be difficult and costly. Keeping the anticipated construction problems and the associated heavy cost in mind, a desilting arrangement for Nathpa-Jhakri project is proposed in the river itself. The effectiveness of this alternative system has been studied through model studies and the cost comparison of this system to the underground desilting system is also made. A hydraulic scale model of the sediment control system of Nathpa-Jhakri hydroelectric project has been constructed. Experiments have been conducted after reproduction of prototype features in the model with pre-determined sediment concentration with varying design discharges and flushing discharges to determine the efficiency of desilting chamber with hoppers at the bottom. Also, approximate cost of alternative sediment control system is calculated on the basis of analysis of rates, given in the Modified Project Report (1986). The sediment removal efficiency of this system is found up to the desired limit. The cost of this system is estimated to be approximately 24% of the cost of underground desilting arrangement as proposed by Himachal Pradesh State Electricity Board (HPSEB).
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1989
Keywords: Sediment control; Hydraulic models